2004
DOI: 10.1007/s00520-004-0667-5
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patients with septic shock: mortality predictors and neutropenia

Abstract: Septic shock among cancer patients admitted to the ICU has a mortality rate similar to that reported for mixed populations, and it is particularly increased when hepatic or respiratory dysfunction develop. Neutropenia on admission does not seem to modify outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 29 publications
2
31
1
Order By: Relevance
“…Neutropenia was not found to affect mortality in cancer patients with Streptococcus pneumoniae bacteraemia [12], as well as bacteraemia caused by other micro-organisms [13]. In line with these data, five other studies evaluating patients hospitalised in ICU showed neutropenia to not be independently associated with mortality in cancer patients with different sites of infection [14][15][16][17][18]. During the past decades, the attention in management of infections in cancer patients has focused on fever and neutropenia [19].…”
Section: Discussionmentioning
confidence: 86%
“…Neutropenia was not found to affect mortality in cancer patients with Streptococcus pneumoniae bacteraemia [12], as well as bacteraemia caused by other micro-organisms [13]. In line with these data, five other studies evaluating patients hospitalised in ICU showed neutropenia to not be independently associated with mortality in cancer patients with different sites of infection [14][15][16][17][18]. During the past decades, the attention in management of infections in cancer patients has focused on fever and neutropenia [19].…”
Section: Discussionmentioning
confidence: 86%
“…Intheliterature,respiratoryfailure(41-45%)andsepsis(24-33%) were the main reasons for an ICU admission and the ICUmortalityrankedbetween30and69%inthesepatients [1][2][3]. Nevertheless, an ICU stay may bridge a transitory complication and thus donate lifetime even to patients with advancedmalignantdiseases.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, Soares et al [18] reported a 44% of mortality rate in a cancer group admitted at ICU due to medical causes, not specifically to sepsis, which accounted only for 15% of admissions. Other authors such as Staudinger et al [27], Regazzoni et al [28], and Rosolem et al [29] reported an ICU mortality rate of 62%, 53.4%, and 51 % in septic patients with cancer admitted at the ICU, respectively.…”
Section: Discussionmentioning
confidence: 96%